2004
DOI: 10.1128/cdli.11.4.766-769.2004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hairpin-Shaped Primer Assay To Study the Association of the −44 Single-Nucleotide Polymorphism of theDEFB1Gene with Early-Onset Periodontal Disease

Abstract: A powerful, cost-effective new method for studying single-nucleotide polymorphisms (SNPs) is described. This method is based on the use of hairpin-shaped primers (HP), which give a sensitive and specific PCR amplification of each specific allele, without the use of costly fluorophore-labeled probes and any post-PCR manipulation. The amplification is monitored in real-time using SYBR Green I dye and takes only 2 h to yield results. The HP assay has a simple design and utilizes a conventional real-time PCR appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
0
23
1
Order By: Relevance
“…The robustness of these data was further supported by a separate analysis of the two parodontopathic distinct forms: CP and AgP. Both independent case populations differed only marginally in terms of allele frequencies and contributed in a Earlier studies on periodontitis investigated associations of SNP G-20A (rs11362) 20 and C-44G (rs1800972) 19 with patients with severe CP and those with early onset periodontitis (currently most likely classified as AgP), respectively. These studies were of much smaller sample size than this study and observed no disease association.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The robustness of these data was further supported by a separate analysis of the two parodontopathic distinct forms: CP and AgP. Both independent case populations differed only marginally in terms of allele frequencies and contributed in a Earlier studies on periodontitis investigated associations of SNP G-20A (rs11362) 20 and C-44G (rs1800972) 19 with patients with severe CP and those with early onset periodontitis (currently most likely classified as AgP), respectively. These studies were of much smaller sample size than this study and observed no disease association.…”
Section: Discussionmentioning
confidence: 88%
“…In earlier studies, the promoter SNPs: G-20A (rs11362) 20 and C-44G (rs1800972) 19 were subjected to candidate gene association studies in patients with severe CP and early onset periodontitis. In these studies, no association with periodontitis was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ''mutant'' promoter contains the second most common base (C) at position À688 and (G) at À44. These variants are prevalent in the population (1,5). Promoter deletion constructs were made to include a variable amount of upstream sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Defensins are classified into a-defensins, h-defensins, and u-defensins according to the size and binding patterns of disulfide bonds within mature peptides. To date, six h-defensins have been identified and mapped to a locus on chromosome 8p, an area that contains at least three separate tumor suppressor genes inactivated during the progression of human malignancies, including prostate and renal cancers (1)(2)(3). Previous studies have revealed that deletion of chromosome 8p is the most common genetic alteration in prostate cancer and the second most common genomic event in bladder and renal cancers (4).…”
Section: Introductionmentioning
confidence: 99%